Land Use and Deforestation in Southeastern Brazil 1753-18401 - Soares de Freitas, Frederico Santos (Fronteira: Journal of Social, Technological and Environmental Science, 2013)
This article analyzes the pressure of farming on tropical forests in eighteenth- and nineteenth-century Brazil. Making use of GIS technology, it was possible to create a map for the South Central of the Minas Gerais province and geocode historical data for agriculture and livestock production. We have found an association between corn and swine production in areas of forest, and we suggest a correlation of the practices of slash-and-burn agriculture, pig raising, and trade of foodstuff to the clearing of forested land.